Precordial T-Wave Inversions in Patients with Arrhythmogenic Right Ventricular Cardiomyopathy Who Present with the Initial Features of Right Ventricular Outflow Tract Arrhythmia - Chung, Fa-Po (Acta Cardiol Sin, 2020)
BACKGROUND: Precordial T-wave inversion (TWI) is an important diagnostic criterion for arrhythmogenic right ventricular cardiomyopathy (ARVC). OBJECTIVE: This study aimed to characterize the initial repolarization features of definite ARVC in patients who first presented with right ventricular outflow tract ventricular arrhythmia (RVOT-VA) and TWI. METHODS: Patients who presented with RVOT-VA and TWI ≥ V(2) were retrospectively assessed. The initial characteristics of repolarization between patients with and without a final diagnosis of definite ARVC during follow-up were compared. RESULTS: TWI ≥ V(2) was observed in 61 of 553 patients (mean age: 44.1 ± 14.7 years; 14 men) with RVOT-VAs. After an average follow-up time of 54.9 ± 33.7 months, 31 (50.8%) patients were classified into the definite ARVC group and 30 (49.2%) into the non-definite ARVC group. The disappearance of precordial TWI ≥ V(2) was observed in eight (13.1%) patients after the elimination of RVOT-VAs. In a multivariate analysis of the initial electrocardiogram features, only fragmented QRS [odds ratio (OR): 15.45, 95% confidence interval (CI): 1.61-148.26, p = 0.02] and precordial V(2) TpTe interval (OR: 1.03, 95% CI: 1.01-1.06, p = 0.02) could independently predict definite ARVC during longitudinal follow-up. An initial V(2) TpTe cutoff value > 88.5 ms could predict the final diagnosis of definite ARVC, with a sensitivity and specificity of 74.2% and 78.6%, respectively. CONCLUSIONS: Despite the high risk of ARVC in RVOT-VAs and TWI ≥ V(2), "normalization" of TWI was observed after ventricular arrhythmia elimination in 13.1% of the patients. Fragmented QRS and longer V(2) TpTe interval were associated with definite ARVC during longitudinal follow-up.